Linguistic Representation of Sensory Experience in EFL Descriptive Texts - Atika Salman Paris; M. Wahyu Hadi (LPPM Institut Pendidikan Nusantara Global, 2026)
This study investigates the linguistic representation of sensory experience in EFL descriptive texts through the analysis of sensory-related lexical expressions employed by EFL learners in descriptive writing. The study aims to identify the types of sensory expressions used in EFL descriptive texts, analyze how sensory experiences are linguistically represented through lexical and descriptive features, and examine the contribution of sensory language to the construction of descriptive meaning. This study employed a qualitative descriptive design with a linguistic analysis approach. The data consisted of 30 descriptive texts written by undergraduate EFL students on various themes, including tourism destinations, people, food, houses, pets, and campus environments. The data were collected through writing tasks and analyzed using qualitative content analysis and lexical categorization techniques. The identified sensory expressions were classified into five categories, namely visual, tactile, auditory, olfactory, and gustatory categories. The findings revealed that students actively employed sensory vocabulary to construct descriptive imagery, experiential meaning, and environmental atmosphere within their texts. Visual sensory expressions emerged as the most dominant category, followed by tactile and auditory expressions, while olfactory and gustatory categories appeared less frequently. The study also demonstrated that sensory language was commonly realized through adjective-noun combinations, descriptive modifiers, and experiential clauses. Furthermore, the findings indicate that sensory representation in EFL descriptive writing is closely related to experiential familiarity, lexical availability, and embodied perception. Sensory vocabulary functioned not only as lexical enrichment but also as an important linguistic resource for constructing vividness, emotional engagement, and descriptive meaning. This study contributes to discussions on sensory linguistics, descriptive discourse, and linguistic representation in EFL contexts by demonstrating how learners transform sensory perception into written language. The findings also provide practical implications for EFL writing instruction, particularly in promoting sensory vocabulary development and experiential language use in descriptive writing practices.